Return To Workplace Fears During Covid-19 (European Journal of Behavioral Sciences, 2022)
This article reports the observations of fear in the workforce while returning to the workplace following the SARS-CoV-2 (COVID-19) pandemic in comparison to previous research on fear in the workplace. Additionally, the findings contribute to the body of knowledge of workplace fears following collective, traumatic events. For the study, a sample of 189 employees were asked 16 questions which were measured on a Likert-type scale, in addition to a free response question on fear management strategies. Distributions of participants encompassed all levels of management. Results indicate primary return to workplace fears of conveying disease to loved ones and national mismanagement of crisis. Additional analysis indicates significant increases in fears stemming from coworker mistrust and career advancement inhibition with decreased fears of being laid off or fired, over baseline conditions. Further, the study observes significant increases in coping strategies such as nutrition and social problem management (such as therapy and socializing) and a decrease in problem management via cognitive adjustments or disengagement. This research suggests that employers take care when crafting their return-to-work strategies to foster trust among coworkers, facilitate opportunities to collectively reflect on traumatic experiences, and provide flexibility in accommodations for individuals’ unique circumstances.